2004
DOI: 10.1002/app.21177
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic elastomers based on recycled high‐density polyethylene, ethylene–propylene–diene monomer rubber, and ground tire rubber

Abstract: High-performance thermoplastic elastomers (TPEs), based on recycled high-density polyethylene (HD-PE R ), olefinic type ethylene-propylene-diene monomer rubber (EPDM), and ground tire rubber (GTR) treated with bitumen, were prepared by using dynamic vulcanization technology, and their structure-property relationships were investigated. It was established that special pretreatment of GTR by bitumen confers outstanding mechanical properties on the resulting TPEs. TPEs, containing GTR pretreated by bitumen, exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 22 publications
2
68
0
Order By: Relevance
“…However, these blends have high concentrations of GTR phase (80% in mass), a recycled material, what may have deteriorated the mechanical properties. Grigoryeva et al [53] produced dynamically vulcanized blends using GTR, and in some of the production methods used by the authors, TPVs were also not obtained. According to the authors, in these cases there was not an effective interfacial stress transference between the phases, and not an entanglement of the GTR rubber chains into the surrounding matrix.…”
Section: Luo and Isayevmentioning
confidence: 99%
“…However, these blends have high concentrations of GTR phase (80% in mass), a recycled material, what may have deteriorated the mechanical properties. Grigoryeva et al [53] produced dynamically vulcanized blends using GTR, and in some of the production methods used by the authors, TPVs were also not obtained. According to the authors, in these cases there was not an effective interfacial stress transference between the phases, and not an entanglement of the GTR rubber chains into the surrounding matrix.…”
Section: Luo and Isayevmentioning
confidence: 99%
“…Several attempts have been made in order to compatibilize GRT and thermoplastic blends. Reactive and non-reactive compatibilization methods, GRT surface modifications based on acid treatments, UV or gamma irradiation, plasma or corona charge, and new methods for preparation of these blends such as: solid-state shear pulverization and solid state mechanochemical millings have been described in the literature [2,7,8] . The resulting materials present mechanical properties more or less similar to those presented by thermoplastic elastomers.…”
Section: -Thermoplastic Elastomers Blends Based On Linear Low Densitymentioning
confidence: 99%
“…Grigoryeva et al [8] prepared thermoplastic elastomers based on recycled high density polyethylene (HDPE), EPDM and GRT treated with bitumen. They concluded that bitumen acts simultaneously as a curing agent for the rubber components (EPDM/GRT) and as a compatibilizer for the blend components.…”
Section: -Thermoplastic Elastomers Blends Based On Linear Low Densitymentioning
confidence: 99%
“…Other interesting solution is the devulcanization of the NR to produce lower molar mass products. Many papers and reviews [78][79][80][81] are devoted to reclaiming processes of postconsumer vulcanized rubber, as, for example, ground tire rubber [78][79][80][81][82][83][84][85][86][87] . Specifically about the products of the degradation of the non-vulcanized NR, many applications are already find in the literature, as following.…”
Section: Application Of the Products Of Degradation Of Nrmentioning
confidence: 99%